2023
DOI: 10.3390/curroncol30090571
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the True Cost of Breast Cancer Treatment: Molecular Subtype and Stage-Specific per-Case Activity-Based Costing

Anna N. Wilkinson,
Jean M. Seely,
Moira Rushton
et al.

Abstract: Background: Breast cancer (BC) treatment is rapidly evolving with new and costly therapeutics. Existing costing models have a limited ability to capture current treatment costs. We used an Activity-Based Costing (ABC) method to determine a per-case cost for BC treatment by stage and molecular subtype. Methods: ABC was used to proportionally integrate multidisciplinary evidence-based patient and provider treatment options for BC, yielding a per-case cost for the total duration of treatment by stage and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Of course, there is also an increase in the total number of screening examinations that must be performed. This has implication on costs and the resources required to conduct the screening; however, as suggested in the recent work of Wilkinson et al, a substantial fraction of these costs could be offset by a reduction of the cost of treating Stage 3 and 4 cancers through earlier detection [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, there is also an increase in the total number of screening examinations that must be performed. This has implication on costs and the resources required to conduct the screening; however, as suggested in the recent work of Wilkinson et al, a substantial fraction of these costs could be offset by a reduction of the cost of treating Stage 3 and 4 cancers through earlier detection [20].…”
Section: Discussionmentioning
confidence: 99%
“…The model also has the provision of calculating costs of screening and therapy for cost-effectiveness studies; however, as indicated by Wilkinson et al, the treatment costs currently used in the model are now out of date and require revision to reflect current practice [20].…”
Section: Discussionmentioning
confidence: 99%
“…In 52.5% of cases, the malignant disease in Serbia is diagnosed in an advanced stage (III-b or IV) with regional and distant metastases ( 18 ). Since the costs of breast cancer treatment is progressively increasing with new expensive therapy options and better progression free survivals and overall survivals, there is an exponential increase in treatment costs, especially for later stages of illness ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…In recent work our colleagues have assembled a table of current costs for breast cancer screening and for treatment of breast cancers of each subtype and stage. 10 We have incorporated these data into user scenarios for the OncoSim Breast model. It has been demonstrated previously that both the cost of screening a population and the benefit (lives saved or years of life gained) will increase when screening begins at an earlier age, ends at an older age and is conducted more frequently (e.g, annually rather than bi-or triennially).…”
Section: Cost-effectivenessmentioning
confidence: 99%